The Warren Buffett Way Workbook - Hagstrom, Robert G., 1956- and Rhoads, Russell (Hoboken, New Jersey John Wiley, 2013)
The Warren Buffett Way Workbook consists of over 500 questions and answers to help readers of The Warren Buffett Way reinforce and cement their knowledge of Buffett s hugely successful investment approach.
Keywords: Investments -- Buffett, Warren -- United States